2018
DOI: 10.1002/ccd.27927
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic durability of transcatheter aortic valves using the updated Valve Academic Research Consortium‐2 criteria

Abstract: Objectives We investigated the hemodynamic durability of the transcatheter aortic valves (TAVs) using the updated Valve Academic Research Consortium‐2 (VARC‐2) criteria. Background The updated VARC‐2 consensus criteria combine flow‐dependent and flow‐independent echocardiographic parameters for hemodynamic assessment of TAVR. Data on the hemodynamic durability of TAV and clinical risk factors associated with valve hemodynamic deterioration (VHD) are lacking. Methods All patients (n = 276) who received TAV betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Our preference was to use a self-expanding valve to allow significant oversizing while limiting the risk of annular rupture; we therefore elected to use a 34-mm TAVI, which is suitable for up to a 30-mm annular diameter and a 94.2-mm perimeter. Use of this valve in native pure AR (NPAR) has been previously reported in small numbers of patients with reasonable success rates ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preference was to use a self-expanding valve to allow significant oversizing while limiting the risk of annular rupture; we therefore elected to use a 34-mm TAVI, which is suitable for up to a 30-mm annular diameter and a 94.2-mm perimeter. Use of this valve in native pure AR (NPAR) has been previously reported in small numbers of patients with reasonable success rates ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to acknowledge that across all studies of TAVI for NPAR, the success rates are considerably lower than contemporary trials of TAVI for AS. Three recent studies reported device success rates ranging from 74.3% to 85% according to Valve Academic Research Consortium (VARC-2) criteria ( 2 , 4 , 5 , 6 ). The main reported complications were high rates of second valve implantation and significant post-procedural AR.…”
Section: Discussionmentioning
confidence: 99%
“…Current expert consensus recommends antiplatelet therapy following TAVR to reduce risk of stroke 17 . A previous report also showed that antiplatelet therapy, but not anti‐coagulation was associated with lower risk of valve degeneration after TAVR 18 . The GALILEO trial (NCT02556203) was halted when early data demonstrated that an anticoagulation (Rivaroxaban) strategy after TAVR was associated with higher incidence of death, bleeding and thromboembolic events when compared to antiplatelet based strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Overall device success according to Valve Academic Research Consortium (VARC-2) criteria was 67%, being higher with NGD (82% versus 47% when compared with EGD). [9] NGD use was associated with less valve malpositioning and less moderate to severe post-procedural AR. Cardiovascular mortality was also lower with NGD.…”
Section: Tavi For Npar: Evidence On New Generation Devicesmentioning
confidence: 99%
“…This leaves unanswered questions about valve durability; as far as we know the incidence of structural valve deterioration after 5 years is very low, but information beyond this time is scarce. [9–12]…”
mentioning
confidence: 99%